2017
DOI: 10.1016/j.cad.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Interactive modeling of complex geometric details based on empirical mode decomposition for multi-scale 3D shapes

Abstract: In this paper we develop an interactive modeling system for complex geometric details transformation based on empirical mode decomposition (EMD) on multi-scale 3D shapes. Given two models, we aim to transfer geometric details from one model to another one in an interactive manner. Taking full advantages of the multi-scale representation computed via EMD, different-scale geometric details can be transferred individually or in a concerted way, which makes our algorithm much more flexible than cut-and-paste and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Given target shapes, viewpoints and space restrictions, Zhang et al [18] find a global optimal surface that delivers the desired appearance when observed from the designated viewpoints, which could guarantee exact depth bounds of per-vertex. Zhang et al [19] treat an input object as a continuous relief depth map and use mesh intersection to paste the relief on the target object based on empirical mode decomposition in multi-scale levels [20].…”
Section: D Model-based Methodsmentioning
confidence: 99%
“…Given target shapes, viewpoints and space restrictions, Zhang et al [18] find a global optimal surface that delivers the desired appearance when observed from the designated viewpoints, which could guarantee exact depth bounds of per-vertex. Zhang et al [19] treat an input object as a continuous relief depth map and use mesh intersection to paste the relief on the target object based on empirical mode decomposition in multi-scale levels [20].…”
Section: D Model-based Methodsmentioning
confidence: 99%
“…Their method preserved target details into the overall shape of a target model, whereas the source model details can also be interfered by the target model. Zhang et al reconstructed an input object as a continuous relief depth map and used mesh intersection to paste the relief on the goal object. In contrast to their method, we do not require the model to be converted into depth maps, and the processes are more concise.…”
Section: Related Workmentioning
confidence: 99%